Leadership and management effectiveness: A multi‐frame, multi‐sector analysis - Bolman, Lee G.; Deal, Terrence E. (Human Resource Management, 1991)
AbstractBolman and Deal (1984, 1991) have developed four perspectives, or frames, for understanding organizations and leadership: structural, human resource, political, and symbolic. This paper reports two studies that operationalize that model. The first study uses critical incidents written by managers to assess how many and which frames they use. Most incidents show the use of one or two frames; very few contain all four. In every population, the structural frame was used frequently while the symbolic frame was rarely evident. Across different populations, the use of the human resource and political frames varied substantially. The second study used survey instruments to assess managers' frame orientations. Regression analyses show that their orientations, as perceived by colleagues, are differentially related to perceived effectiveness as manager and leader. Managerial effectiveness is related to an emphasis on rationality and organizational structure. Leadership effectiveness is linked to symbols and culture. For men and women in comparable positions, gender is unrelated to leadership orientations or to their effectiveness as managers or leaders.